2010
DOI: 10.1029/2009jg000944
|View full text |Cite
|
Sign up to set email alerts
|

Role of stormflow in reducing N retention in a suburban forested watershed, western Japan

Abstract: [1] To evaluate the role of stormflow in reducing N retention in forested watersheds, we investigated the inorganic N budget of a Japanese suburban forested watershed for 4 years where the proportion of direct flow to precipitation is considerably high (mean is 33%; range is 25-42%). Soil net N mineralization and net nitrification were also measured at middle and lower positions of a slope within the watershed to evaluate nitrate (NO 3 − ) pool size. Annual mean N deposition via throughfall plus stemflow was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 97 publications
(156 reference statements)
1
14
0
Order By: Relevance
“…Elevated levels of atmospheric N deposition have been reported in the urban and suburban areas of the Fukuoka metropolitan area (Fig. 1b) located near the YEW (Chiwa et al, 2010b, 2012). Elevated atmospheric N deposition due to long‐range transport of nitrogenous pollutants from the east Asian continent has also been reported (Morino et al, 2011; Chiwa et al, 2012; Chiwa et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Elevated levels of atmospheric N deposition have been reported in the urban and suburban areas of the Fukuoka metropolitan area (Fig. 1b) located near the YEW (Chiwa et al, 2010b, 2012). Elevated atmospheric N deposition due to long‐range transport of nitrogenous pollutants from the east Asian continent has also been reported (Morino et al, 2011; Chiwa et al, 2012; Chiwa et al, 2013).…”
Section: Discussionmentioning
confidence: 92%
“…However, it remains unclear why the annual exportation of NO 3 − was higher than N deposition. Bulk precipitation often considerably underestimates dry deposition (Lindberg et al, 1986; Chiwa et al, 2010b). Therefore, dry deposition should be measured to evaluate precise N budgets in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…All statistical analyses were carried out using an open source statistical programing language of R Version 3.3.3. in urban-or suburban-forested watersheds compared with rural-forested watersheds [10,25,26], and regional-scale spatial patterns of higher atmospheric N deposition were observed in urbanor suburban-forested areas [27][28][29]. In a previous study, river basins included suburban forests, and atmospheric N deposition was moderately high (16 kg N ha −1 year −1 in these areas [30]), which is above the threshold value that could potentially cause N leaching from a forested watershed. Therefore, in the present study, upland forests in the river basins were influential NPSs of N for downstream areas.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this view, low concentrations of NO 3 in stream water from 100% forested areas were observed (Figure 4). Chronic high atmospheric N deposition generally causes N saturation in forested ecosystems, resulting in high NO 3 concentrations in stream water from forested watersheds (Dise and Wright, 1995;Aber et al, 1998; Chiwa et al, 2010;Chiwa et al, 2012). Such high N leaching causes N eutrophication downstream (Chiwa et al, 2012).…”
Section: Effects Of Agricultural Activities On Atmospheric N and P Dementioning
confidence: 99%
“…Many studies, however, have indicated that high atmospheric N deposition may cause N saturation in forested ecosystems, resulting in high NO 3 À concentrations in stream water from forested watersheds (Dise and Wright, 1995;Aber et al, 1998;Chiwa et al, 2010;Chiwa et al, 2012). Agricultural activities can increase atmospheric N deposition in nearby forests because of high ammonia (NH 3 ) emissions originating from livestock and fertilizer (Boxman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%